HUBUNGAN OBESITAS SENTRAL DENGAN KEJADIAN DIABETES MELITUS TIPE 2: LITERATURE REVIEW - Yunita Yunita (PENA NURSING, 2022)
Background: Type 2 diabetes mellitus is a non-communicable disease that causes almost 70% of deaths. The riskiest factor for type 2 diabetes mellitus is the type of central obesity. Objective: To analyze the relationship between central obesity and the incidence of type 2 diabetes mellitus. Methods: literature review, eight works of literature from google scholar and Science Direct for the years 2010-2021. The design of the research article is a cross-sectional study and a case-control study with a population of adult type 2 diabetes mellitus patients. Articles were analyzed using the JBI Critical Appraisal Tools Checklist for Cross-Sectional Studies and for Case-Control studies that met the criteria. Results: Central obesity was significantly associated with the incidence of type 2 diabetes mellitus which was strongly associated with general obesity. Discussion: Seven of the eight articles stated that there was a significant relationship between central obesity and the incidence of type 2 diabetes mellitus, but it was as strong as general obesity. Central obesity and general obesity are associated with the incidence of type 2 diabetes mellitus.